The morphological signs of plants of white cabbage (Brassica oleraceae L. convar. capitata (L.) Alef. var. alba DC) and their variability depending on type of sort - О. Я. Жук (Plant Varieties Studying and Protection)
Indicators of the morphological signs of type of sort on white cabbage plants Dutch flat, Belarus, Amager, Langendijker winter and their variability are the presented. It is established low and average factor of a variation at the majority of the morphological signs. Strong high-quality and ecological variability of signs “height external rake” and “its size leafy parts” at type of sort Dutch flat is defined.